Echocardiographic diagnosis of permanent pacemaker lead malposition in the left ventricle: A case study. Issue 12 (20th November 2020) - Luke, Peter; Shepherd, Ewen; Irvine, Tim; Duncan, Rae
Abstract: Inadvertent endocardial lead malposition is recognized as a rare incident which is usually underreported and if recognized during implantation can be easily corrected. This phenomenon is caused by the ventricular lead unintentionally crossing a pre‐existing patent foremen ovale, septal defects (atrial or ventricular) or directly from the aorta via an accidental subclavian puncture resulting in the lead implanting into the left ventricle. While this is a rare occurrence we report, the incidental finding of pacemaker lead malposition during a routine follow‐up transthoracic echocardiogram and the benefits of three‐dimensional transesophageal echocardiography in this patient prior to lead extraction.